Targeted treatments in advanced renal cell carcinoma: focus on axitinib - Verzoni E; Grassi P; Testa I; Iacovelli R; Biondani P; Garanzini E; De Braud F; Procopio G (Dove Medical Press, 2014)
Elena Verzoni, Paolo Grassi, Isabella Testa, Roberto Iacovelli, Pamela Biondani, Enrico Garanzini , Filippo De Braud, Giuseppe ProcopioDepartment of Medical Oncology 1, Fondazione IRCCS Istituto Nazionale Tumori, Milan, ItalyAbstract: Antiangiogenesis options have evolved rapidly in the last few years, with an increasing number of agents currently approved by the US Food and Drug Administration and European Medicines Agency. Angiogenesis inhibitors have been shown to be very effective for the treatment of metastatic renal cancer cell. Axitinib is a third-generation inhibitor of vascular endothelial growth factor receptor and is currently being developed for the treatment of various malignancies. The pharmacokinetic properties of axitinib may have a selective therapeutic effect, with minimal adverse reactions and enhanced safety. In a large Phase III study of previously treated patients with metastatic renal cell carcinoma, axitinib achieved a longer progression-free survival than sorafenib with an acceptable safety profile and good quality of life. This review focuses on the pharmacology, pharmacokinetics, and clinical activity of axitinib in the current treatment of renal cell carcinoma. The role of axitinib in the adjuvant and/or neoadjuvant setting needs to be evaluated in further clinical trials.Keywords: axitinib, renal cell carcinoma, vascular endothelial growth factor receptor, angiogenesis